Molecular and functional analysis of the mce4 operon in Mycobacterium smegmatis. (24th August 2017) - García‐Fernández, Julia; Papavinasasundaram, Kadamba; Galán, Beatriz; Sassetti, Christopher M.; García, José L.
Summary: Mycobacterium smegmatis contains 6 homologous mce (mammalian cell entry) operons which have been proposed to encode ABC‐like import systems. The mce operons encode up to 10 different proteins of unknown function that are not present in conventional ABC transporters. We have analysed the consequences of individually deleting each of the genes of the mce4 operon of M. smegmatis, which mediates the transport of cholesterol. None of the mce4 mutants were able to grow in cholesterol suggesting that all these genes are required for its uptake and that none of them can be replaced by the homologous genes of the other mce operons. This result suggests that different mce operons do not provide redundant capabilities and that M. smegmatis, in contrast with Mycobacterium tuberculosis, is not able to use alternative systems to import cholesterol in the analysed culture conditions. Either deletion of the entire mce4 operon or single point mutations that eliminate the transport function cause a phenotype similar to the one observed in a mutant lacking all 6 mce operons suggesting a pleiotropic role for this system.